Growth and enzymatic activity of Leucoagaricus gongylophorus, a mutualistic fungus isolated from the leaf‐cutting ant Atta mexicana, on cellulose and lignocellulosic biomass. (4th July 2017) - Vigueras, G.; Paredes‐Hernández, D.; Revah, S.; Valenzuela, J.; Olivares‐Hernández, R.; Le Borgne, S.
Abstract: A mutualistic fungus of the leaf‐cutting ant Atta mexicana was isolated and identified as Leucoagaricus gongylophorus . This isolate had a close phylogenetic relationship with L. gongylophorus fungi cultivated by other leaf‐cutting ants as determined by ITS sequencing. A subcolony started with 500 A. mexicana workers could process 2 g day −1 of plant material and generate a 135 cm 3 fungus garden in 160 days. The presence of gongylidia structures of 35 μ m was observed on the tip of the hyphae. The fungus could grow without ants on semi‐solid cultures with α ‐cellulose and microcrystalline cellulose and in solid‐state cultures with grass and sugarcane bagasse, as sole sources of carbon. The maximum CO2 production rate on grass ( V max = 17·5 mg CO2 Lg −1 day −1 ) was three times higher than on sugarcane bagasse ( V max = 6·6 mg CO2 Lg −1 day −1 ). Recoveries of 32·9 mgglucose gbiomass −1 and 12·3 mgglucose gbiomass −1 were obtained from the fungal biomass and the fungus garden, respectively. Endoglucanase activity was detected on carboxymethylcellulose agar plates. This is the first study reporting the growth of L . gongylophorus from A. mexicana on cellulose and plant material. Significance and Impact of the Study: According to the best of our knowledge, this is the first report about the growth of Leucoagaricus gongylophorus, isolated from the colony of the ant Atta mexicana, on semisolid medium with cellulose and solid‐state cultures with lignocellulosic materials. The maximum CO2 production rate on grass was three times higher than on sugarcane bagasse. Endoglucanase activity was detected and it was possible to recover glucose from the fungal gongylidia. The cellulolytic activity could be used to process lignocellulosic residues and obtain sugar or valuable products, but more work is needed in this direction. Abstract : Significance and Impact of the Study: According to the best of our knowledge, this is the first report about the growth of Leucoagaricus gongylophorus, isolated from the colony of the ant Atta mexicana, on semisolid medium with cellulose and solid‐state cultures with lignocellulosic materials. The maximum CO2 production rate on grass was three times higher than on sugarcane bagasse. Endoglucanase activity was detected and it was possible to recover glucose from the fungal gongylidia. The cellulolytic activity could be used to process lignocellulosic residues and obtain sugar or valuable products, but more work is needed in this direction.